2016
DOI: 10.1080/15368378.2016.1194290
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low-frequency electromagnetic fields: A possible non-invasive therapeutic tool for spinal cord injury rehabilitation

Abstract: Traumatic insults to the spinal cord induce both immediate mechanical damage and subsequent tissue degeneration. The latter involves a range of events namely cellular disturbance, homeostatic imbalance, ionic and neurotransmitters derangement that ultimately result in loss of sensorimotor functions. The targets for improving function after spinal cord injury (SCI) are mainly directed toward limiting these secondary injury events. Extremely low-frequency electromagnetic field (ELF-EMF) is a possible non-invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 147 publications
0
10
0
Order By: Relevance
“…ELF-EMF therapy has been noted for the minimal level of harm it causes, the extensive range of ways in which it can be used to treat various diseases, as well as the beneficial clinical results achieved with relatively small financial outlay. The nature of the ELF-EMF effect on the body allows deep tissue penetration, however, it is not a thermal method, which makes it possible to use it in the treatment of neurological diseases [17]. ELF-EMF affects the body at both the molecular and cellular level and causes the change in ionic channels.…”
Section: Introductionmentioning
confidence: 99%
“…ELF-EMF therapy has been noted for the minimal level of harm it causes, the extensive range of ways in which it can be used to treat various diseases, as well as the beneficial clinical results achieved with relatively small financial outlay. The nature of the ELF-EMF effect on the body allows deep tissue penetration, however, it is not a thermal method, which makes it possible to use it in the treatment of neurological diseases [17]. ELF-EMF affects the body at both the molecular and cellular level and causes the change in ionic channels.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have shown that electrical stimulation can guide the neurite growth in vitro and enhance neuron survival and locomotor function improvement of injured spinal cord in vivo (Han et al., 2016b, Hofstoetter et al., 2018, Yao and Li, 2016, Zhang et al., 2017). However, a disadvantage of spinal electrical stimulation is the need for surgery and an implanted electrode array, which may have undesirable effects (Kumar et al., 2017). EA is widely used in clinical practice because of its effectiveness and safety for patients.…”
Section: Introductionmentioning
confidence: 99%
“…They are commonly used in neurology, psychiatry (treatment of depression), rheumatology, orthopedics (to treat spinal injury) and dermatology both at diagnostic and therapeutic levels ( D’Angelo et al, 2015 , Mattsson and Simkó, 2019 ). ( Kumar et al, 2017 ). It also promotes cell proliferation ( Song et al, 2018 ) and has supporting role of in generating immune-modulatory responses, neuromodulation and possible benefits of neuroprotection.…”
Section: Extremely Low Frequency Radiation (Elf)mentioning
confidence: 99%